Effects of evening primrose oil on prevention of postpartum grief in primiparous women: A clinical double-blind randomized controlled trial - Soghra Nikoomazhab; Seyyed Mahmoud Latifi; Azam Honarmandpour; Parvin Abedi (Mashhad University of Medical Sciences, 2018)
Introduction: Evening primrose is one of the medicinal herbs with good effects which has been used in the treatment of multiple physical and mental problems and no side effects of its oral consumption has not been reported so far; therefore this study was performed with aim to evaluate the effects of evening primrose oilon prevention of postpartum grief in primiparous women referred to Ahvaz health centers. Methods: This clinical double-blind randomized trial was conducted on 132 primiparous women referred to Ahvaz health centers in 2012-2013. The subjects were randomly divided into two groups of 66 cases to receive a daily dose of 1 gr of evening primrose oil capsule or similar placebo gelatin capsule from the beginning of 37th weeks of pregnancy up to two weeks after delivery. The samples were assessed by Edinburg standard questionnaire on days of 4, 10 and 14 after delivery. Data were analyzed by SPSS software (version 20), and independent t-test, Chi-square and repeated measures analysis test. P<0.05 was considered significant.      Results: There was statistically significant difference between the two groups regarding the risk of the postpartum grief, so that the risk of postpartum grief was lower in the intervention group than the placebo group (P=0.0001). The mean score of Edinburgh test in intervention group was significantly less compared to the control group on postpartum 4th day (p = 0.0001), 10th day (p = 0.001), and 14th day (p = 0.08). Conclusion: The use of evening primrose oil is effective to prevent postpartum grief.